FERTILITY RESPONSE IN POSTPARTUM SUBESTRUS SURTI BUFFALO SUBJECTED TO HEATSYNCH ± PRID FIXED-TIME AI PROTOCOL - SAXENA, S; KHASATIYA, C T; SAVANI, H R; PATEL, M D; KHARADI, V B (The Indian Journal of Animal Reproduction, 2022)
Eighteen postpartum subestrus (>45 d postpartum) Surti buffalo were equally divided into three groups toevaluate the efficacy of fixed time AI (FTAI) protocols viz. Heatsynch and Heatsynch + PRID (ProgesteroneRelease Intra-vaginal Device), and the third group was not subjected to any treatment protocol (control). In bothFTAI groups, the buffalo were administered (i.m.) GnRH analogue (0.01 mg, Inj. Busereline acetate) on day0, PGF2α analogue (500 μg, Inj. Cloprostenol sodium) on day 7 and estradiol benzoate (0.5 mg) on day 8. Inaddition, in Heatsynch + PRID group, intra-vaginal PRID implant (0.96 g, progesterone) was inserted for 7 days.In both FTAI groups, inseminations were carried out twice on day 10. In the control group, inseminations weredone at spontaneous estrus. In all the groups, the buffalo failing to conceive were re-inseminated at subsequentspontaneous estrus. The overall percentage of buffalo getting conceived in Heatsynch, Heatsynch + PRID andcontrol group was 100, 83.3 and 66.7%, respectively. In brief, Heatsynch protocol, being cost effective, can berecommended to improve fertility status of postpartum subestrus Surti buffalo.
Keywords: Buffalo; FTAI; Heatsynch; Subestrus; Surti